Gregory the Great : Ascetic, Pastor, and First Man of Rome - Demacopoulos, George E. (Book collections on Project MUSE., 2015)
In this collection of essays, Gregory the Great emerges as a figure both interpreting and interpreted: interpreting the past; receiving, synthesizing, and developing the teachings of earlier writers; and, by this very process, presenting a persuasive theological and pastoral agenda which itself inspires ongoing projects of interpretation and development in later periods up to and including our own. (Publisher).